TINGKAT%2520KETERAMPILAN%2520DASAR%2520SEPAKBOLA%2520SEKOLAH%2520SEPAKBOLA%2520(SSB)%2520PSDM%2520USIA%252010-12%2520TAHUN%2520KECAMATAN%2520PONGGOK%2520KABUPATEN%2520BLITAR%2520TAHUN%25202019 - FAJAR EKO CAHYONO, BOY; SYAFII, IMAM (Jurnal Prestasi Olahraga, 2019)
ABSTRACT THE LEVEL OF BASIC SKILL OF FOTTBALL STUDENTS OF FOOTBALL SCHILL (SSB) PSDM AGE 10-12 YEARS OLD OF PONGGOK, BLITAR IN 2019 Name : Boy Fajar Eko Cahyono Reg : 15060474110 Study Program : Bachelor of Sport Coaching Education Faculty : Sport Science Institution : State University Of Sport Football is a sport that is played by 11 players with teams facing each other using a grassy field using a tool in the form of a ball, in a basic technique soccer game becomes a very basic thing that must be possessed by every player, while the basic technique includes passing , dribble, control, heading, juggling, trowh in and shooting. Coaching on this basic technique must also be done from an early age and of course also must pass the correct and designed training. This study aims to determine the level of basic skills of PSDM football school students (SSB) aged 10-12 years. The method used is quantitative and presented in descriptive form. The subjects in this study were all students of SSB PSB Ponggok Blitar, aged 10-12 years, 22 children. Data analysis techniques used are the percentage and frequency. The results of each of the basic skills tests for SSB PSDM football are: 1. Dribble There is 1 student in the